1977
DOI: 10.1104/pp.60.5.739
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Regulation of Carbon Metabolism in Photosynthesizing Leaf Discs

Abstract: The over-all process of nitrate reduction and ammonia incorporation into amino acids in higher plant leaves (along with the role of light in that process) has been a subject of recent research (3,10,12). Given the production of amino acids as well as sucrose during photosynthesis (16), it is of interest to determine whether leaf regulatory mechanisms involve ammonia. The intracellular NH4+ level could influence leaf carbon metabolism during photosynthesis with respect to sucrose synthesis versus the amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

1978
1978
1995
1995

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 22 publications
7
45
0
Order By: Relevance
“…Such an effect would be consistent with the increased carbon flux through the Krebs cycle observed in response to exogenously supplied NH4+ (Platt et al, 1977;Larsen et al, 1981). However, NH4+ in the range of 1 to 10 mM did not inhibit PDH kinase in the presence of saturating (10 mM) K+ (data not shown).…”
Section: Dlscusslonsupporting
confidence: 69%
“…Such an effect would be consistent with the increased carbon flux through the Krebs cycle observed in response to exogenously supplied NH4+ (Platt et al, 1977;Larsen et al, 1981). However, NH4+ in the range of 1 to 10 mM did not inhibit PDH kinase in the presence of saturating (10 mM) K+ (data not shown).…”
Section: Dlscusslonsupporting
confidence: 69%
“…8) the low molecular weight pools were significantly more labile during the dark period when high levels of NH: were present, reflecting a significant modification in the metabolism of the contained phytoplankton prior to this time. In recent photosynthesis studies (e. g. Kanazawa et al, 1970;Bassham, 1971 ;Hipkin and Syrett, 1977;Platt et al, 1977;Mohamed and Gnanam, 1979) increased levels of NH: have been shown to lead to modifications of cellular metabolism in response to both enhanced availability of nitrogen and enzyme regulation. Typical influences include increased synthesis of amino acids and protein relative to the production of carbohydrate precursors and polymers.…”
Section: Time Course Of Cellular Materials Incorporationmentioning
confidence: 99%
“…At the same time, ammonia exposure resulted in a much lower water-soluble sugar content than in the control plants during low-temperature acclimation, which again indicates that ammonia taken up by the leaves was metabolized (Platt et al., 1977;Champigny et al, 1992;Lea et al, 1992).…”
Section: Aw Exposure At Low Temperaturesmentioning
confidence: 98%
“…Apparently ammonia w-as taken up by the lea\'es, as has been demonstrated in leaves of Italian ryegrass {Lolivm multifiorum) and poplar {Populus euramericana) (Lockyer & Whitehead,1 986 ;Van Hove et al,1 991) and was subsequently metabolized, as evident from the higher biomass. Ammonia can be assimilated to glutamate by the glutamine/glutamate synthase cycle at the expense of carbohydrates (Platt, Plaut & Bassham, 1977;Champigny et al, 1992;Lea, Blackwell & Joy. 1992).…”
Section: Aw Exposure At Low Temperaturesmentioning
confidence: 99%